2015
DOI: 10.1515/ttj-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

How to Train Safe Drivers: Setting Up and Evaluating a Fatigue Training Program

Abstract: Fatigue is considered as a serious risk driving behavior, causing road accidents, which in many cases involve fatalities and severe injuries. According to CARE database statistics, professional drivers are indicated as a high-risk group to be involved in a fatigue-related accident. Acknowledging these statistics, a training program on driving fatigue was organized, aiming at raising awareness of professional drivers of a leading company in building materials, in Greece. Selected experimental methods were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…When investigating the contribution of several variables to explain commuters' adoption of walking and cycling for the improvement of their health, findings are in line with previous studies (as in Adamos and Nathanail, 2015;Armitage and Conner, 2006;Nathanail and Adamos, 2013), which validate that behavioral intentions and behavioral beliefs are the parameters that mostly affects persons' behavior. Regarding persons' adoption of active travel for the improvement of quality of life, behavioral beliefs are the strongest predictor, while gender affects significantly behavior towards walking, but not cycling.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When investigating the contribution of several variables to explain commuters' adoption of walking and cycling for the improvement of their health, findings are in line with previous studies (as in Adamos and Nathanail, 2015;Armitage and Conner, 2006;Nathanail and Adamos, 2013), which validate that behavioral intentions and behavioral beliefs are the parameters that mostly affects persons' behavior. Regarding persons' adoption of active travel for the improvement of quality of life, behavioral beliefs are the strongest predictor, while gender affects significantly behavior towards walking, but not cycling.…”
Section: Discussionsupporting
confidence: 87%
“…Behavioral beliefs provide the linkage between the behavior of interest and the expected outcomes, behavioral intentions indicate how hard people are willing to try to achieve a goal, descriptive norms reflect what is perceived as common or normal, perceived behavioral control is determined as the person's own perception of how easy or difficult it is to perform the behavior and risk comprehension indicates how dangerous a situation may be (Ajzen, 1991;Deutsch & Gerald, 1955). Past behavior is associated with intention, but the effect, in this case, is indirect and lastly, self-reported behavior is frequently used to understand the mechanisms that affect behavior (Adamos & Nathanail, 2015).…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…drinking a coffee, listening to music and opening the window for fresh air, are presented in Table 9.20. Table 9.20: Bivariate correlations of the individual variables and their relationship with the variable addressing self-reported behavior towards following other solutions to fatigue than stopping and resting when tired (Source: Adamos & Nathanail, 2015). Based on the findings of Table 9.20, it was observed that behavioral belief (BB123), behavioral intention (INT3) and past behavior (PB123, PB4) were significantly correlated with self-reported behavior (B234).…”
Section: Inter-relationships Between Measurement Variablesmentioning
confidence: 97%
“…In addition, it is remarkable that drivers often adopt strategies to deal with fatigue, which are falsely or partially effective, such as drink a coffee, listen to music, open the window for fresh air, etc. (Adamos & Nathanail, 2015;Horne & Reyner, 1988;Reyner & Horne, 1997).…”
Section: The Challenge Of Evaluating Fatigue Road Safety Communication Campaigns and Training Programsmentioning
confidence: 99%
See 1 more Smart Citation